Determining the groundwater potential for agricultural use in Ethiopian Highlands [Abstract only] - Yilak, Debebe L.; Tilahun, Seifu A.; Schmitter, Petra S.; Nakawuka, Prossie; Enku, T.; Kassawmar, N. T.; Steenhuis, Tammo S. (2015)
The Ethiopian government has declared the Lake Tana - Beles region to be a growth corridor and irrigation development is one of the priorities. Since the dry season river flow is limited, groundwater has the greatest potential for increasing irrigation in the near future. The main drawback is lack of information on sustainable groundwater use and specifically the ground water potential. Therefore the objective of this research is to calculate the annual groundwater recharge. The study was conducted in Robit-Bata, an experimental watershed of 911 ha, located at the south-eastern edge of Lake Tana. Farmers have excavated more than 300 hand dug wells for irrigation use from which, we used 50 wells for water table fluctuation observations for one year starting from April, 2014. Daily Precipitation was recorded for the same period. The annual recharge was estimated using the water – level fluctuation method. Specific yield was defined as the difference of porosity and field capacity of the subsurface formation. The annual average areal groundwater recharge was 640 mm/year, which is 41% of the rainfall and ranged from 50mm to 390mm per week for the various locations in the watershed. The greatest recharge amounts were found in the plains at the foot of the hills and river course areas consisting mostly weathered basalt rock. At those locations the groundwater rose steadily during the rainy monsoon phase. Smaller amount of recharge occurred both near the top of the hills with tough rock formation and in the, flat areas near to stream with sandy and clay deposits and groundwater at, shallow well depth. Our study indicates that the current use of the groundwater seems sustainable. Further research is required for optimized utilization of the limited groundwater resources for irrigation development to meet the food security of the community.